ANALISIS IMPLEMENTASI SISTEM KESELAMATAN JALUR KENDARAAN, JALUR PEDESTRIAN, DAN KESELAMATAN PENGEMUDI PADA AREA POOL PT X TAHUN 2022 - Rafael Arfah (2023)
Accidents at workplace involving transportation does not only impact physical disadvantages but also work effectivity and financial loss of a company. PT X is one of the company that engaged in the field of transportation and logistics where potentials of workplace accidents involving tranportations can be found. This study has the purpose of analyzing road safety system, pedestrian walk safety and driver's safety as an effort to increase the prevention of workplace accidents at PT X by comparing to the applicable standards including UU No.22 Tahun 2009, PM 13 Tahun 2014, Permen PU No. 13 Tahun 2011, HSG 136 (Transport Safety) by Health and Safety Executive and General Guide for Traffic Management by Safe Work Australia. This study used analytic qualitative method with using observation and interview to the informants which are HSE head department, drivers, and security of PT X. The results of this study indicate that there is still a contradiction In the applycation of the workplace transportation safety system, namely in the aspects of workplace layout, signs, warnings, marks, transportation road safety,pedestrian walk safety, dan driver.s driving behavior. Suggestions for this workplace is to apply one way road system, install signs and road marks, and improve driver's monitoring and training.